Bacterial colonization of bone substitute materials used in oral surgery: mechanisms, clinical implications, and preventive strategies—A narrative review - Wojciech Popowski; Damian Koseski; Dominika Domanowska; Magdalena Zalewska; Magdalena Popowska (Frontiers in microbiology, 2025)
The advancement of tissue engineering and the development of novel biomaterials have opened new possibilities for the effective treatment of patients with edentulism and other dental deficiencies, as well as for the prosthetic reconstruction and functional rehabilitation of the stomatognathic system. Bone substitute materials are now widely used in orthopedics, reconstructive surgery, and dentistry to support the regeneration of bone tissue lost due to trauma, inflammation, or tooth extraction. However, surgical procedures within the oral cavity inherently carry a risk of postoperative infection, which can impair healing and compromise treatment outcomes. Unlike natural bone regeneration, bone healing following grafting functions as a repair process that may involve partial resorption of the graft material. Such bone deficiencies can hinder prosthetic reconstruction, making the use of bone substitute materials essential for guided bone regeneration. Bone substitutes can be classified as autogenous, allogenic, xenogenic, or alloplastic, each exhibiting distinct osteoinductive and osteoconductive properties. This review discusses the biological and clinical characteristics of these material groups, with particular attention to their susceptibility to colonization by bacterial strains commonly found in the human oral cavity. It also highlights the risks associated with bacterial biofilm formation and examines its implications for the oral microbiome under dysbiotic conditions.